ESG reporting and analysts' recommendations in GCC: The moderation role of royal family directors - Abdulsamad Alazzani; Wan Nordin Wan-Hussin; Michael Jones; Ahmed Al-Hadi (Journal of Risk and Financial Management, 2021)
This study examines whether financial analysts consider or incorporate the environmental, social and governance disclosures (thereafter ESG) in their recommendations. We then test whether royal family directors affect this relation. Using a dataset from six Gulf Cooperation Council (GCC) countries, we find evidence that analysts' recommendations are influenced by ESG information. Further, we find the political connection negatively moderates the relationship between sell-side analysts' recommendations and ESG. This suggests that financial analysts may assess the ESG disclosure in those firms with the political connection of royalty, in GCC countries, as superficial compliance rather than a genuine commitment. Our results are robust when subjected to endogeneity tests.
Keywords: 330; GCC; environmental; investment recommendation; royal family directors; social and governance